Strategies And Policies For Basic Education In Cambodia: History And Development - Chanthea, Out (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2013)
We examine the process of development and change in the state of education in Cambodia over four decades. Some authors argue that during the 1950s and 1960s, efforts to enhance basic education opportunities for all Cambodians were largely unsuccessful due to the lack of adequate infrastructural mechanisms and a guiding framework for action. Of the periods considered in this study, only the Prince Sihanouk regime (1950s-1960s) was relatively socioeconomically advanced, and saw a growth in the number of modern school buildings, teacher training centres, and universities. The succeeding regimes in the 1970s not only failed to maintain the development, but by the second half of the 1970s the formal education system had been completely dismantled. The collapse in 1979 of the Pol Pot regime made way for the rebirth of traditional socio-cultural structures and the wide expansion of schooling opportunities throughout the 1980s. National rehabilitation and reconstruction during the 1980s, despite lingering social insecurity, marked considerable and fundamental progress towards the present educational situation of this struggling nation.